2010
DOI: 10.1097/ncc.0b013e3181c29598
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Monitoring and Self-care Practices Among Oncology Adults in China

Abstract: Patient-reported symptom occurrence and severity scale enable health providers to prioritize, evaluate interventions, and promote/assist patients' self-care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 41 publications
6
48
0
1
Order By: Relevance
“…38 Acupuncture was rarely used by the participants in this study. This finding is consistent with data from a similar study in another part of China, 3 and with data from a published review of the annual use of acupuncture in a metropolitan hospital in the north of China, which found less than 1% incidence of acupuncture used for antiemetic purposes. 39 Thus, although acupuncture is an important component of TCM used in China, it may not be as commonly used for managing NV as might be assumed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…38 Acupuncture was rarely used by the participants in this study. This finding is consistent with data from a similar study in another part of China, 3 and with data from a published review of the annual use of acupuncture in a metropolitan hospital in the north of China, which found less than 1% incidence of acupuncture used for antiemetic purposes. 39 Thus, although acupuncture is an important component of TCM used in China, it may not be as commonly used for managing NV as might be assumed.…”
Section: Discussionsupporting
confidence: 93%
“…A series of studies by Williams and colleagues 3,14Y17 examined cancer symptom self-care strategies, applying the same methodology across a range of countries, including the United States, 14,15 Thailand, 16 the Philippines, 17 and China. 3 Findings from these studies reflect that some practices are consistently used across countries, whereas other practices are not. For example, Chinese participants reported that drinking hot water alleviated vomiting, whereas the Filipino sample reported drinking cold water and holding ice chips in the mouth helped prevent their nausea.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…[7][8][9][10][11]14,19,[25][26][27][28] The questions were about to what degree patients trusted in medical therapy, alternative practices for cure other than medical therapies, and degree of CAM use. The CAM use starting date, reason, benefits of CAM, name of the product, daily dosage and application type, source of the recommendation, the quality of effect, and the cost of CAM were evaluated in the form.…”
Section: Cam Use Formmentioning
confidence: 99%
“…Another investigation showed that white patients tended to vary ways to control their pain, were more proactive in selecting treatments, and were highly individualistic and independent, whereas ethnic minorities de-emphasized pain to achieve normalcy, chose naturalistic modalities for pain management, and were more family-centric [45]. Chinese patients with cancer recruited from cancer centers in China reported frequently using complementary self-care measures in categories of diet/nutrition/lifestyle, mind/body (including distraction [reading]), and massage to treat pain [46].…”
Section: Racial Ethnic and Cultural Preferencesmentioning
confidence: 99%